Ketimpangan pendapatan antarwilayah di Jawa Timur: Peran pertumbuhan ekonomi, belanja daerah, IPM, dan upah minimum - Ariyani Nurul Fadilah; Marseto Marseto (Journal of Economics Research and Policy Studies, 2026)
Income inequality between regions in East Java Province remains an obstacle to equitable development even though economic growth continues to increase, indicating that economic progress is not evenly distributed across the region. The present study examined the extent to which economic growth, regional fiscal expenditure, the Human Development Index, and district-level minimum wages influence income inequality across regencies and municipalities in East Java Province. Income inequality was measured using the Williamson Index. The study employed a quantitative approach with a panel data regression method based on balanced panel data covering 38 districts and cities during the 2020–2024 period, resulting in 190 observations. Empirical results revealed that economic growth and minimum wage both exerted a statistically significant positive influence on income inequality. In contrast, greater allocation of regional fiscal expenditure and improvements in human development were found to serve as effective mechanisms in narrowing interregional income disparities within East Java Province.